PERAN PARTAI POLITIK PENGUSUNG DALAM PEMENANGAN CALON KEPALA DAERAH DI KABUPATEN MAGETAN - Noviano Suyide (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
Abstract— This research aims to analyze the role of supporting political parties in winning Regional Head Candidates in Magetan Regency. This research is normative research using conceptual studies (conceptual approach) and statutory studies (statute approach). The role of the supporting party in winning the regional head candidate in the 2018 - 2023 Magetan Regency Pilkada. Where the main function of a political party is to seek and maintain power in order to realize programs prepared based on a certain ideology. The method used by a political party in a democratic political system to gain and maintain power is to participate in general elections. Or in this context it is the regional elections which are held every 5 years in Magetan Regency. Based on the data obtained from this research, the role of political parties in Magetan Regency in the regional head election process can be explained as follows, namely: Candidate Selection Process, Registration of candidate pairs with the Magetan Regency KPUD, Campaign, Voting and vote counting.